2019
DOI: 10.1007/s11085-019-09905-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Oxide Scale Formed on T12 Water Wall Tube After Long-term Service in Supercritical Power Plant

Abstract: Oxide scale control is one of the critical maintenance issues in fossil fuel power plant. Hence, the water treatment of the feed water has been changed from all-volatile treatment (AVT) to oxygenated treatment (OT) by added some amount of oxygen in the system to form a stable oxide and minimize the scale growth rate. In this work, the oxide scales formed on T12 water wall tube after one cycle of chemical cleaning treatment under OT condition in a supercritical coal power plant were characterized by using vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This is an evidence for that the Cr can diffuse outward through the oxide scale and then result in the formation Cr-rich haematite layer. It was also found that the oxide scale formed on the inner surface of the T12 water wall tube after long-term service in supercritical fossil power plant contains Cr-rich α-Fe 2 O 3 oxides [10]. However, the oxygen content in the actual operation condition is about 100 ppb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an evidence for that the Cr can diffuse outward through the oxide scale and then result in the formation Cr-rich haematite layer. It was also found that the oxide scale formed on the inner surface of the T12 water wall tube after long-term service in supercritical fossil power plant contains Cr-rich α-Fe 2 O 3 oxides [10]. However, the oxygen content in the actual operation condition is about 100 ppb.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports focused on the corrosion behaviour of F-M steels in SCW at the temperature range of 400-650 °C showed that the oxidation process followed parabolic oxidation kinetics and the oxide scales consisted of multi-layer structures with Cr-rich inner layer and Fe-rich outer layer [4 9]. In our previous work, the Cr-rich haematite layer was observed in the oxide scale formed on the T12 water wall tube after long-term service in supercritical fossil power plant with temperature of 430 °C for 164171 h [10]. The Cr-rich haematite layer was also observed in our lab tests in simulated SCW environment with DO = 3 ppm [11].…”
Section: Introductionmentioning
confidence: 99%